High and Low Taxa Specificity of Rhizosphere Bacteria Communities of Mangrove (Rhizophora mucronata) from Kuala Langsa and Telaga Tujuh Island, East Aceh - Siti Maysaroh; Meutia Samira Ismet; Rita Andini; Nurlita Anggraini; Beginer Subhan (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research